Relationship Between Ubiquitin-Specific Peptidase 18 and Hypertension in Polish Adult Male Subjects: A Cross-Sectional Pilot Study - Dziamałek-Macioszczyk, Paulina; Harazny, Joanna M.; Kwella, Norbert; Wojtacha, Paweł; Jung, Susanne; Dienemann, Thomas; Schmieder, Roland E.; Stompór, Tomasz (Medical science monitor, 2020)
BACKGROUND Arterial hypertension (HT) is a leading cause of cardiac hypertrophy and heart failure. Ubiquitin-specific peptidase 18 (USP18) has been recently described as a factor that prevents myocardial dysfunction. The present study measured serum USP18 levels in normotensive (n=29), isolated diastolic hypertensive (n=20), and systolic-diastolic hypertensive (n=30) male participants and correlated these results with biochemical parameters that are included in routine assessments of patients with hypertension. MATERIAL AND METHODS Seventy-nine men, aged 24 to 82 years (mean=50.8±11.4 years), were included in the study. None of the participants had ever been treated for HT. Blood and urine parameters were assessed using routine techniques. Serum USP18 levels were measured by enzyme-linked immunosorbent assay. RESULTS The means and 95% confidence intervals (CIs) of USP18 levels in the HT(-), iDHT(+), and HT(+) groups were 69.3 (22.1-116.5) pg/ml, 90.1 (29.0-151.3) pg/ml, and 426.7 (163.1-690.3) pg/ml, respectively. In the HT(+) group, the mean serum USP18 level was 6.2-times higher than in the HT(-) group (p=0.014) and 4.7-times higher than in the iDHT(+) group (p=0.19). The partial correlation analysis that was adjusted for risk factors of arteriosclerosis indicated that USP18 levels were correlated with systolic blood pressure, pulse pressure, and heart rate. CONCLUSIONS This preliminary study found that serum USP18 levels were significantly higher in drug-naive male participants with arterial hypertension compared with normotensive controls. USP18 exerts cardiovascular-protective effects. Elevations of USP18 levels may indicate a counterregulatory process that is engaged during increases in pressure in the left ventricle.